Prognostic significance of CKAP2L expression in patients with clear cell renal cell carcinoma - Liu, Zhi; Zhang, Jun; Shen, Deyun; Hu, Xuechun; Ke, Zongpan; Ehrich Lister, I Nyoman; Sihombing, Bungaran (Frontiers in Genetics, 2023)
Background Cytoskeleton-associated protein 2-like protein (CKAP2L) is thought to promote the progression of glioma, breast cancer and ovarian cancer. However, the role of CKAP2L in clear cell renal cell carcinoma (ccRCC) is still unclear. The study aimed to investigate the roles and mechanisms of CKAP2L in ccRCC. Methods The level of CKAP2L in tumors was explored by using UALCAN and Oncomine databases. Gene expression datasets of ccRCC from TCGA and GEO were also used to validate the CKAP2L level in ccRCC. Survival analysis was performed to investigate the relationship between CKAP2L level and prognosis of ccRCC patients. Cox regression analysis was used for identifying the independent prognostic factors. GSEA, GSVA, protein–protein interaction analysis, co-expression analysis and immune infiltration analysis were used to explore the potential mechanisms of CKPA2L in ccRCC. Moreover, the levels of CKAP2L in clinical ccRCC tissues were also measured using RT-PCR, immunohistochemical analysis and western blotting. M1 Macrophages and CD4+ T cells were also detected by IHC between tumor and normal tissues. Results The level of CKAP2L was upregulated in ccRCC according to multiple databases and experimental verification. Upregulated CKAP2L is an independent prognostic factor, which might activate the JAK-STAT signaling pathway, the P53 signaling pathway, the TGF-β signaling pathway, the WNT signaling pathway, etc., in ccRCC. Protein–protein interaction analysis and co-expression analysis suggest that CKAP2L might interact with some proliferation proteins. Immune infiltration analysis indicates that CKAP2L may affect the level of activated CD4+ memory T cells, M1 macrophages, CD8+ T cells, and neutrophils in ccRCC. More M1 macrophages infiltrations in tumor tissues with higher CKAP2L was validated by ccRCC tumor tissues. Conclusions CKAP2L is upregulated in ccRCC tissues, which may promote progression of the disease. CKAP2L is a potential target for prognostic markers and a potential treatment target in ccRCC.